PENGABDIAN MASYARAKAT MELALUI PENYULUHAN FINANCIAL TECHNOLOGY DALAM MENGELOLA KEUANGAN KELUARGA PADA IBU RUMAH TANGGA DI DESA PAMEGARSARI – BOGOR - Khoirunnisa Azzahra; Baiq Fitri Arianti; Siti Chaerunisa P.; Anggun Putri R.; Irwan Setiawan (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2019)
The community service activity through the counseling of Financial Technology knowledge in Pamegarsari village aims to resolve the problem of partners from the Pamegarsari Village Government, namely the large number of people affected by cases of fake transactions and online loans and online shopping fraud. To overcome these problems, we as a lecturer in the Accounting Study Program at the University of Pamulang carry out Community Service using counseling methods about the importance of Financial Technology knowledge in managing family finances. From the overall implementation of PKM can provide an understanding of Financial Technology through this counseling showed excellent results including; first the participants consisting of housewives in Pamegarsari Village welcomed positively and enthusiastically in the implementation of this PKM activity; Secondly, the increased understanding and knowledge of participants about the importance of financial technology in managing family finances is indicated by their questions and responses when conducting discussions with speakers at the time the activity took place. And third; the high expectation of participants so that the intensity of counseling or similar activities is often carried out in pamegarsari village.